(untitled) (Journal of Asian Development Studies, 2015)
This study empirically investigates the impact of Foreign Direct Investment (FDI) on Energy Intensity (EI) in case of South Asia by using panel data set over the period of 1990 to 2013. To achieve this objective, Least Square Dummy Variable Model (LSDV), Fixed Effect Model (FEM) and Random Effect Model (REM) are used and for model selection we incorporated efficiency test (F-test) and Hausman specification test. Energy saving is important because it saves money but also help to produce more goods with less energy, FDI is one of the key channel with which energy knowledge spillover take place and economic growth happened. On the basis of Hausman specification test and model efficiency test we concluded that Fixed effect model is an appropriate model in which FDI remain insignificant with negative sign. So our results remain in line with previous literature on the subject. In our analysis, we have seen that FDI inflows are not responsible for the EI of the South Asia, since it depends also on other economic factors. In other words, South Asian countries emphasis on the attitude that needs to develop in order to attract and benefit from more FDI inflows and also use of issue-linkages, as for intended by the Kyoto Protocol (clean development mechanism), which explain such FDI that brings energy reducing technology transfer, which should be encouraged.